Mengembangkan Jiwa Kepemimpinan dalam Berwirausaha di Era Globalisasi - Sewang Sewang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
In the ever-evolving era of globalization, leadership skills in entrepreneurship have become increasingly crucial for business practitioners. This article aims to develop and strengthen leadership qualities within the entrepreneurial context through a community service program. This program is designed to provide training and guidance to local entrepreneurs, specifically students at SMK Kartika XX-1 Makassar, with a focus on developing leadership skills, business management, and adaptation to global changes. The methods employed in this program include workshops, mentoring, and realistic business simulations. The results of the program indicate a significant improvement in the leadership abilities and business performance of the participants. Furthermore, the program helps entrepreneurs become better prepared to face challenges and seize opportunities in the global market. These findings demonstrate that with the right approach, leadership qualities can be effectively developed within the entrepreneurial community, thereby contributing to sustainable local economic growth.